ANALISIS “MARKETING 3.0” PADA PERUSAHAAN PT. RADIO SUARA INDRAKILA (KR RADIO 107,2 FM) YOGYAKARTA - Agung Sulistyo (Universitas Muhammadiyah Semarang, 2017)
The success of a company or establishment, cannot be separated from a variety of factors, both internal factors and external factors. Similarly, KR Radio, the radio station continues to exist conduct their activities using a variety of strategies. This study aims to determine the analysisMarketing Concept 3.0 at PT. Radio Voice Indrakila (KR Radio) Yogyakarta in the face of competition. According to Kotler, Kartajaya and Setiawan in a book entitled